An Analysis of Co-relation between Intelligence, Education & Crime: Exploring the Relationship between Intelligence, Education, and Criminal Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Intelligence is one of the cognitive dimensions of personality. A great number of prior researchhave found that the criminal population's intellect is lower, particularly in terms of verbal intelligence. Thegoal of this research is to see if there is a relationship between intellect and criminal conduct, and if so,how it manifests itself. Criminal detainees from the Republic of Srpska's Correctional Institutes and theCourt Department of Psychiatry Clinic Sokolac participated in the study, which included murder and nonhomicideactions. A test group of 60 convicts who had committed homicide (homicide offenders) and acontrol group of 60 inmates who had not committed homicide participated in the study (non-homicideoffenders). The research was conducted in a controlled, transverse, or cross-sectional fashion. Inmates(homicidal and non-homicidal) had an average IQ of 95.7. Homicide offenders had an IQ of 97.4 while nonhomicideinmates had an IQ of 94.09. The intelligence coefficients for non-homicide inmate groupingswere as follows robbery offenders (IQ 96.9), theft perpetrators (IQ 93.83), and other criminal offenders (IQ93.83). (IQ 92.8). Homicide convicts had a verbal intellectual capacity of 91.22, whereas non-homicideoffenders had a verbal intellectual ability of 91.10. In the non-verbal or manipulative section, intellectualabilities were average, but they were higher in the murder inmates group (IQm 103.65) than in the nonhomicideinmates group (IQm 103.65). (IQm 97.08). Inmates under investigation (homicide and nonhomicide)had lower average intellect than the general community. The verbal component of intellect islower than normal, but the nonverbal component is average.